Influence of graphene quantum dots on electrical properties of polymer composites. (26th July 2017) - Arthisree, D; Joshi, Girish M
Abstract: We successfully prepared synthetic nanocomposite (SNC) by dispersing graphene quantum dots (GQD) in cellulose acetate (CA) polymer system. The dispersion and occupied network of GQD were foreseen by microscopic techniques. The variation of plane to crossed linked array network was observed by the polarizing optical microscopic (POM) technique. The scanning electron microscopy (SEM) revealed the leaves like impressions of GQD in host polymer system. The series network of GQD occupied in CA at higher resolution was confirmed by transmission electron microscopy (TEM). The two dimensional (2D) topographic images demonstrated an entangled polymer network to plane morphology. The variation in surface roughness was evaluated from the dimensional (3D) topography. The influence of temperature on AC conductivity with highest value (4  ×  10 −5 S cm −1 ), contributes to the decrease in activation energy. The DC conductivity obeys the percolation criteria co-related to the GQD loading by weight fraction. Furthermore, this synthetic nanocomposite is feasible for the development of sensing and electrical applications.